The silver pony : a story in pictures - Ward, Lynd, 1905-1985. (Boston : Houghton Mifflin, 1973)
Recounts without words the adventures of a boy and his winged horse.
Booklist
Library Journal
Wilson's Children
K-3
K-3
Keywords: Fairy tales -- Illustrations; Stories without words; Fairy tales; Stories without words; Fairy tales; Stories without words